2002
DOI: 10.1128/jcm.40.5.1698-1704.2002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microbiological Study of Human Carious Dentine by Culture and Real-Time PCR: Association of Anaerobes with Histopathological Changes in Chronic Pulpitis

Abstract: The bacteria found in carious dentine were correlated with the tissue response of the dental pulps of 65 teeth extracted from patients with advanced caries and pulpitis. Standardized homogenates of carious dentine were plated onto selective and nonselective media under anaerobic and microaerophilic conditions. In addition, real-time PCR was used to quantify the recovery of anaerobic bacteria. Primers and fluorogenic probes were designed to detect the total anaerobic microbial load, the genera Prevotella and Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
194
1
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(229 citation statements)
references
References 38 publications
25
194
1
9
Order By: Relevance
“…Bacteria numbers calculated using the calibration curves prepared by this procedure may therefore be more accurate. Subgingival plaque samples have frequently been collected using paper points (13,(19)(20)(21). Although the sample amount is smaller than that collected by devices such as scalers, reproducibility is high, and the accuracy of testing is reportedly sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria numbers calculated using the calibration curves prepared by this procedure may therefore be more accurate. Subgingival plaque samples have frequently been collected using paper points (13,(19)(20)(21). Although the sample amount is smaller than that collected by devices such as scalers, reproducibility is high, and the accuracy of testing is reportedly sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Various authors have identified species of lactobacilli found in carious tissues. [4][5][6][7] Although the adhesive properties of lactobacilli are not remarkable, it has been shown that they were also able to adhere to various cell cultures involving a certain level of specificity. 8 This specificity is related to the lactobacilli protein S-layer in the cell surfaces, which has a crystalline structure responsible for the surface hydrophobicity.…”
mentioning
confidence: 99%
“…DIAGNOdent is thus considered a gold standard for measuring the progression of caries. In many previous studies, bacterial culture [20][21][22] or PCR methods 23,24) have been used to evaluate bacterial infection in caries lesions. However, bacterial culture and PCR cannot be used to quantitatively analyze the amount of bacteria in dentinal tissue because the amount of dentin subjected to these methods cannot be controlled accurately 6) .…”
Section: Discussionmentioning
confidence: 99%